Complete androgen insensitivity (syndrome of Morris): A case - Fajardo, María (2015)
Testicular feminization is a recessive genetic disorder linked to the X chromosome with complete androgen insensitivity, the most common form of male pseudohermaphroditism. The production of androgens by the testes is normal but there is no action for lack of receptors in the target organs. Individuals 46, XY show both testicles, female external genitals, vagina blind end and no miileriano derivative. The incidence is about 2 to 5 per 100,000, the phenotype is female. A catered event is presented in the Maternal Perinatal Institute in 2003, in the study and management who was for several specialties.